Aquicultura familiar no município de Mogeiro/Paraíba - Cavalheiro, Thiago Brandão (2021)
Aquaculture is an important economic activity for the Northeast region of Brazil. Paraiba is consolidated and has great economic importance in the two producing poles: Coastal Region and in the Paraiba River Valley. In this region, the municipality of Mogeiro was chosen, in the wild of Paraiba, where the Novo Mundo settlement is located, which has 27 family farmers. The riverine population of fishermen and microfarmers has been promoting a change of behavior, in which fishermen have migrated their activity to aquaculture. Issues related to productivity (health,water resources management), as well as to identify and evaluate the local ecological knowledge (CEL) precursor of this behavior change in the study region. We will hold shrimp farming management workshops, as well as conservation and environmental recovery activities with fish farmers. Finishing the work with the elaboration of a shrimp cultivation management class. The productivity among the evaluated producers varied between 1150 and 3200 kg/ha, showing great variation and associated with the different managements employed, as well as the amplitudes of variation in the parameters and above all the reports of the occurrence of diseases are factors involved.